2021
DOI: 10.24191/ajue.v16i4.11953
|View full text |Cite
|
Sign up to set email alerts
|

School Resource Center and Students’ Civilization in Digital Age

Abstract: In the 21st century, the School Resource Centre (SRC) is essential as an innovative educational practice that supports teaching-learning in the digital age. Previous studies have highlighted the beneficial roles of an SRC in terms of collections, SRC programs, and the provision of a conducive learning environment to school communities. However, due to the meaningful impact of technology, SRCs need to transform their traditional roles to more modern roles in the digital age in order to bring knowledge that is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The information landscape is rapidly evolving and Australian youth need the opportunity to develop the capabilities to navigate our contemporary and changing society (Department of Education and Training, 2018). Building students' information literacy is important to ensure they can effectively participate in formal education but also to manage everyday life contexts that require seeking, evaluating and using information (Polizzi, 2020;Shuhidan et al, 2021;Taala et al, 2019).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…The information landscape is rapidly evolving and Australian youth need the opportunity to develop the capabilities to navigate our contemporary and changing society (Department of Education and Training, 2018). Building students' information literacy is important to ensure they can effectively participate in formal education but also to manage everyday life contexts that require seeking, evaluating and using information (Polizzi, 2020;Shuhidan et al, 2021;Taala et al, 2019).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…Since then, digital literacy training has become teachers' global professional development component. Several scholars have reported that the integration of digital tools and resources into teaching methodologies has become essential to meet the evolving needs of 21st-century learners (Bondarenko & Gudkova, 2023;Dancsa et al, 2023;Hafeez, 2021;McWhorter, 2021;Nikolova & Evtimova, 2022;Ng et al, 2022;Shuhidan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%